A method for preparing Cu (I) halide scintillation single crystal, thin film for X-ray imaging
Patent Information
- Application Number
- CN202611044771.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]本发明旨在解决现有溶液法制备有机-无机杂化Cu (Ⅰ)基卤化物单晶生长尺寸小、内部缺陷多、结晶质量差难题,提供一种具有大尺寸、高结晶质量且光产额高的闪烁单晶,以满足高分辨单晶X射线成像的需求
[0042]1.本发明提供的用于X射线成像的Cu (Ⅰ)基卤化物闪烁体具有零维电子结构,具备强烈的激子限域作用,可有效抑制非辐射复合;其晶体结构中大空间位阻的有机阳离子形成了天然疏水层,具备良好的水稳定性。
Smart Images

Figure CN122879829A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of X-ray imaging technology, specifically relating to a method for preparing Cu(I)-based halide scintillation single crystals and thin films for X-ray imaging. Background Technology
[0002] X-ray imaging technology has been widely applied in medical diagnostics, industrial non-destructive testing, and emerging wearable radiation monitoring. The core of high-resolution and high-performance imaging technology lies in scintillator materials. With the continuous expansion of application scenarios, an ideal scintillator not only needs to balance high light yield, low afterglow, low detection limit, and high spatial resolution, but also places extremely high demands on material flexibility and operational stability in extreme environments. Currently, commercial X-ray detection equipment still mainly relies on traditional inorganic scintillators, such as NaI:Tl, CsI:Tl, and BGO. These materials typically have high effective atomic numbers and strong X-ray absorption capabilities, resulting in extremely high energy conversion efficiency. However, these materials usually rely on high-temperature melting processes such as the Bridgman process, which are not only energy-intensive and time-consuming, but also produce rigid single crystals that cannot meet the needs of flexible detection. Furthermore, NaI:Tl and CsI:Tl are highly hygroscopic, requiring expensive and complex packaging processes. BGO, on the other hand, suffers from low light yield and its luminescence performance is greatly affected by temperature, making the development of novel X-ray scintillator materials an urgent priority.
[0003] In recent years, organic-inorganic hybrid Cu(I)-based halides have emerged as strong contenders for next-generation high-performance scintillators due to their unique low-dimensional structure, highly tunable luminescence properties, and low-cost solution processing capabilities. In these hybrid materials, inorganic metal halide clusters are effectively isolated by organic cations, forming a strong exciton confinement effect and a self-trapped exciton (STE) emission mechanism, which endows the material with high light output. Furthermore, by introducing organic cations with large steric hindrance, an efficient hydrophobic physical barrier is constructed at the crystal lattice level, thereby endowing the material with excellent water stability and enabling underwater X-ray imaging. However, the current solution-based preparation of organic-inorganic hybrid Cu(I)-based halide single crystals still faces bottlenecks such as small crystal size, numerous internal defects, and insufficient crystal quality to meet the requirements of single-crystal X-ray imaging. Meanwhile, how to composite these materials with polymer matrices to achieve flexible, large-area scintillator films that can even operate stably in extreme underwater environments while maintaining high light transmittance remains a pressing challenge in this field. Summary of the Invention
[0004] This invention aims to solve the problems of small size, numerous internal defects, and poor crystallinity in the growth of organic-inorganic hybrid Cu(I)-based halide single crystals prepared by existing solution methods. It provides a scintillation single crystal with large size, high crystallinity, and high light yield to meet the requirements of high-resolution single-crystal X-ray imaging. Simultaneously, this invention overcomes the shortcomings of existing luminescent thin films that are difficult to operate stably in extreme environments. By dissolving the aforementioned single crystal and in-situ compositing it with a polymer matrix, a scintillation composite thin film with high transmittance, large-area flexibility, and excellent water stability is provided, thereby achieving high-resolution underwater X-ray imaging.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystal, characterized by its chemical formula (C... 21 H 22 P)2Cu2I4 has a molecular weight of 1245.5, a monoclinic crystal system, and a space group of P21 / n.
[0007] The scintillation single crystal is a bulk single crystal with a size on the order of centimeters, and has organic cations (C) 21 H 22 P) + isolation Zero-dimensional electronic structure formed by anion clusters.
[0008] Furthermore, the unit cell parameters of the scintillation single crystal are: a=11.6046Å, b=12.3378Å, c=15.3372Å, α=90°, β=94.732°, γ=90°;
[0009] The half-width at half maximum (WHM) of the X-ray diffraction rocking curve of the (101) crystal plane of the scintillation single crystal is 65.04″.
[0010] There will be slight fluctuations in the unit cell parameters of all single crystals prepared by the method of this invention. This is due to the ambient temperature during testing, instrument system errors, microscopic defects in the crystal, and errors during structural refinement. According to general rules, the fluctuation of each axis length is ≤ ±0.05 Å, the fluctuation of the angle is ≤ ±0.5°, the crystal quality and microstructure are basically constant, and the full width at half maximum (FWHM) will only fluctuate within a very small range. In crystallography, these slight differences do not affect that they belong to the same crystal phase.
[0011] This invention also provides a method for preparing the above-mentioned zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystal, which is characterized by employing a gradient growth strategy combining seed crystal induction and solvent evaporation growth, including the following steps:
[0012] S1, Preparation of the first precursor solution
[0013] Isopropyltriphenylphosphine C 21 H 22 PI and cuprous iodide CuI were dissolved in a mixed solution of N,N-dimethylformamide DMF and formic acid HCOOH, sealed with a sealing film, and heated and stirred at 40-45℃ to obtain a nearly saturated first precursor solution.
[0014] S2, Seed Crystal Acquisition
[0015] The first precursor solution was filtered, sealed with a sealing membrane, and an opening was made in the sealing membrane. It was then volatilized at a constant temperature of 40-45℃ for 96-120 h to obtain single crystals of millimeter size. Single crystals were then selected from these to serve as seed crystals.
[0016] S3, Micro-redissolution treatment
[0017] The seed crystal is placed in a nearly saturated second precursor solution, sealed with a sealing film, and kept at a constant temperature of 30-35°C. After the seed crystal undergoes slight re-dissolution, it begins to grow.
[0018] Among them, C 21 H 22 PI and CuI are dissolved in a mixed solution of N,N-dimethylformamide and formic acid, sealed with a sealing film, and heated and stirred at 30-35℃ to obtain a second precursor solution;
[0019] C 21 H 22 The solubility of PI in DMF is positively correlated with temperature; the higher the temperature, the greater the solubility. Since the first precursor solution was prepared at a higher temperature than the second precursor solution, the solubility of the second precursor solution (C2) is higher. 21 H 22 The molar concentration of PI in N,N-dimethylformamide is lower than that in the first precursor solution. 21 H 22 Molar concentration of PI in N,N-dimethylformamide;
[0020] S4, Quasi-equilibrium growth
[0021] After the seed crystal growth in S3 is restricted, a hole is made in the sealing film, the solvent begins to evaporate, and the single crystal continues to grow. After the single crystal growth is restricted, it is removed, washed, and vacuum dried to obtain centimeter-sized (C) crystals. 21 H 22 P)2Cu2I4 single crystal.
[0022] Further, in S1, C in the first precursor solution 21 H 22 The molar ratio of PI to CuI is 1:1; the volume ratio of N,N-dimethylformamide to formic acid is 9-18; C 21 H 22The molar concentration of PI in DMF was 0.1-0.15 mol / L; the stirring method was magnetic stirring, the speed was set to 100-1000 r / min, the stirring time was 10-12 h, and water bath heating was used;
[0023] In S2, the first precursor solution is filtered using an organic nylon-66 needle filter with a pore size of 0.22 μm; the size of the opening formed by the central puncture of the sealing membrane is 1-1.5 mm; it is volatilized at a constant temperature in a water bath; the seed crystal selection criteria are transparency and absence of visible impurities and growth defects;
[0024] In S3, C in the second precursor solution 21 H 22 The molar ratio of PI to CuI is 1:1, the volume ratio of N,N-dimethylformamide to formic acid is 9-18, and C... 21 H 22 The molar concentration of PI in DMF is 0.05-0.1 mol / L; it is kept at a constant temperature in a water bath.
[0025] In S4, the seed crystal growth restriction means that the seed crystal size does not change with the naked eye within 12 hours, and the size of the opening formed by the puncture in the center of the sealing film is 1-1.5 mm.
[0026] The term "limited single crystal growth" refers to the absence of any visible change in single crystal size within 12 hours. The crystal is then removed from the solution, washed 3-5 times with isopropanol, and placed in a vacuum drying oven at 40-45°C for 4-6 hours.
[0027] This invention provides a Cu(I)-based halide scintillation film, characterized in that it is formed by in-situ composite of the above-mentioned zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystal with a polymethyl methacrylate (PMMA) matrix after dissolution. The scintillation film exhibits high transmittance under ambient light, emits bright blue light under X-ray excitation, and retains X-ray imaging capability in water.
[0028] The method for preparing the above-mentioned Cu(I)-based halide scintillation thin film is characterized by including the following steps:
[0029] 1) Dissolve the above Cu(I)-based halide scintillation single crystal in a mixed solution of N,N-dimethylformamide and formic acid, seal the solution with a sealing film, and heat and stir to obtain a precursor solution;
[0030] 2) Add polymethyl methacrylate powder to the precursor solution, heat and stir to obtain a latex-like suspension;
[0031] 3) The latex-like suspension is coated onto a substrate to form a film, which is then annealed and peeled off to obtain a Cu(I)-based halide scintillation film, i.e., (C21 H 22 P)2Cu2I4@PMMA flexible scintillator film.
[0032] Further, in step 1), the volume ratio of N,N-dimethylformamide to formic acid is 9-18, (C 21 H 22 The mass concentration of P)2Cu2I4 in N,N-dimethylformamide is 0.05-0.1 g / mL; the stirring method is magnetic stirring, the speed is set to 100-1000 r / min, the stirring time is 2-4 h, and the water bath heating is carried out at a temperature of 60-65℃.
[0033] In step 2), polymethyl methacrylate powder and (C 21 H 22 The mass ratio of P)2Cu2I4 single crystals is 3-4. The stirring method is magnetic stirring, the speed is set to 100-1000 r / min, the stirring time is 2-4h, and water bath heating is used with a heating temperature of 60-65℃.
[0034] In step 3), the annealing temperature is 75-80℃ and the annealing time is 20-30min.
[0035] Furthermore, the present invention also provides the application of the above-mentioned zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystal in the preparation of X-ray imaging devices, and the application of the above-mentioned Cu(I)-based halide scintillation thin film in X-ray imaging or the preparation of X-ray imaging devices in air or underwater environments.
[0036] Based on the above applications, the present invention provides an X-ray imaging device, which is characterized in that its detection material is the above-mentioned zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystal or the above-mentioned Cu(I)-based halide scintillation thin film.
[0037] The concept and principle of this invention:
[0038] The (C) prepared by this invention 21 H 22 P)₂Cu₂I₄ is a typical organic-inorganic hybrid metal halide. Structurally, its inorganic component... Clusters are covered by large-sized organic cations (C 21 H 22 P) + Complete isolation creates a zero-dimensional electronic structure in space. This structure leads to a strong exciton confinement effect, suppressing nonradiative recombination and thus endowing the material with high light yield.
[0039] To obtain high-quality, large-size single crystals suitable for X-ray detection, this invention employs a gradient growth strategy combining seed-induced growth and solvent evaporation. Millimeter-sized seed crystals are obtained through rapid evaporation. Immersing these seed crystals in a near-saturated precursor solution allows for micro-dissolution, eliminating minute defects and adhering microcrystals on the seed crystal surface and exposing clean crystal faces, laying the foundation for high-quality single crystal growth. During solvent evaporation, the evaporation rate is controlled by temperature control and openings in a sealed membrane, maintaining the precursor solution at a low supersaturation level. This quasi-equilibrium growth effectively reduces internal stress and dislocations in the crystal, ultimately yielding centimeter-sized single crystals with excellent crystallinity.
[0040] The isopropyltriphenylphosphine cation selected in this invention (C 21 H 22 P) + These organic ligands possess significant hydrophobic groups and substantial steric hindrance. During crystal growth and film deposition, they densely surround the inorganic luminescent centers, forming a natural hydrophobic shielding layer. This not only prevents water molecules from attacking the unstable Cu-I bonds but also, through excellent compatibility with the PMMA matrix, creates a dense, waterproof encapsulation structure within the film. This is the core physical mechanism for achieving long-lasting underwater X-ray imaging.
[0041] The advantages of this invention are:
[0042] 1. The Cu(I)-based halide scintillator for X-ray imaging provided by the present invention has a zero-dimensional electronic structure and strong exciton confinement effect, which can effectively suppress non-radiative recombination; the organic cations with large steric hindrance in its crystal structure form a natural hydrophobic layer, which has good water stability.
[0043] 2. The method for preparing Cu(I)-based halide scintillation single crystals and thin films provided by this invention has simple steps and does not involve dangerous or complex processes. The single crystals prepared using a gradient growth strategy combining seed crystal induction and solvent evaporation can reach centimeter-scale sizes, possessing clear crystallographic planes and excellent crystal quality. The composite thin film prepared by the in-situ method of dissolving the single crystal involves an in-situ crystallization process. Under the spatial confinement of PMMA, the in-situ precipitated microcrystals are uniform in size, do not agglomerate, and possess high transmittance and uniform luminescence, significantly superior to traditional physically blended thin films. Traditional physically blended thin films have uneven size distribution and are prone to agglomeration and gravitational settling. Large agglomerated particles cause severe light scattering, reducing imaging resolution.
[0044] 3. The scintillation single crystal prepared by this invention emits bright blue light under X-ray excitation, exhibiting high light yield and low detection limit, enabling high-resolution imaging for X-ray imaging. The prepared thin film demonstrates excellent X-ray imaging capabilities in both air and water.
[0045] 4. This invention employs a gradient crystallization strategy of seed crystal induction and solvent evaporation to prepare target single crystals. These crystals are large in size, high in quality, and emit blue light, making them compatible with the detection bands of commonly used commercial photodetectors. Therefore, single crystals paired with photodetectors (such as APDs) can achieve excellent X-ray imaging results. Furthermore, from the perspective of single crystal growth technology, this invention utilizes a rapid growth process that significantly shortens the growth cycle. In conventional crystal growth processes, such as in a evaporation environment of 30-35°C without the introduction of seed crystals, the time to obtain crystals of a considerable size through slow solution evaporation is approximately 15-20 days. In contrast, this invention can obtain several millimeter-sized single crystals in 4-5 days (96-120 hours). Attached Figure Description
[0046] Figure 1 (C) prepared in Example 1 21 H 22 Crystal structure diagram of P)2Cu2I4 single crystal;
[0047] Figure 2 (C) prepared in Example 1 21 H 22 Schematic diagram of the crystal growth process of P)2Cu2I4 single crystal;
[0048] Figure 3 (C) prepared in Example 1 21 H 22 XRD analysis of P)2Cu2I4 single crystal: (a) Comparison of single crystal, powder and simulated XRD spectra; (b) X-ray rocking curve;
[0049] Figure 4 (C) prepared in Example 1 21 H 22 Scintillation properties of P)2Cu2I4 single crystal: (a) Radioluminescence (RL) spectrum, with an inset showing the luminescence of the single crystal under X-ray excitation at 50 kV and 80 μA; (b) Light yield assessment; (c) Calculation results of dose rate-dependent integrated RL intensity and detection limit; (d) X-ray image of a key using the prepared single crystal.
[0050] Figure 5 The (C) prepared in Example 2 21 H 22 Photographs of P)2Cu2I4@PMMA flexible thin film under ambient light and X-rays;
[0051] Figure 6Spatial resolution evaluation of the thin film prepared in Example 2: (a) is an image of the standard line pair card (Type 39b) and intensity distribution curves at 8, 9, and 10 LP / mm; (b) is a modulation transfer function (MTF) curve obtained based on the edge-cutting method.
[0052] Figure 7 This is an X-ray image of the iron wire inside the capsule obtained using the thin film prepared in Example 2;
[0053] Figure 8 The diagram shows the underwater X-ray imaging device based on the thin film prepared in Example 2 and the underwater X-ray imaging diagram of the chip.
[0054] Figure 9 The (C) prepared in Comparative Example 1 21 H 22 Photographs of P)2Cu2I4 crystals;
[0055] Figure 10 For the (C) prepared in Comparative Example 2 21 H 22 Photographs of P)2Cu2I4@PMMA flexible thin films under ambient light and X-rays. Detailed Implementation
[0056] The following is a further detailed description of the present invention in conjunction with the accompanying drawings and specific embodiments:
[0057] Example 1
[0058] A method for preparing Cu(I)-based halide scintillation single crystals for X-ray imaging includes the following steps:
[0059] S1. Place C 21 H 22 PI powder (2 mmol, 0.8646 g), CuI powder (2 mmol, 0.3809 g), DMF (18 ml) and HCOOH (2 ml) were mixed in a 50 ml beaker, a magnetic stir bar was added, the beaker was sealed with a sealing film, and the beaker was placed on a magnetic stirrer and stirred at 600 r / min for 12 h in a water bath at 40 °C to dissolve the first precursor solution.
[0060] S2. The first precursor solution was drawn using a disposable syringe. The needle was then replaced with an organic nylon-66 filter with a pore size of 0.22 μm. The solution was filtered into a clean 50 ml beaker, sealed with a sealing membrane, and a small hole with a pore size of 1 mm was punctured in the center of the sealing membrane with a needle. The beaker was then placed in a water bath at 40°C for rapid constant temperature evaporation. After 96 hours, millimeter-sized single crystals were obtained.
[0061] S3. Place C 21 H22 PI powder (2 mmol, 0.8646 g), CuI powder (2 mmol, 0.3809 g), DMF (20.5 ml), and HCOOH (2 ml) were mixed in a 50 ml beaker, a magnetic stir bar was added, the beaker was sealed with a sealing film, and the beaker was placed on a magnetic stirrer and stirred at 600 r / min for 12 h in a water bath at 30 °C to obtain the second precursor solution. Using clean stainless steel tweezers, transparent single crystals without visible impurities and growth defects were selected from the millimeter-sized single crystals obtained in S2 as seed crystals. The seed crystals were then placed into the second precursor solution and sealed with a sealing film.
[0062] S4. Place the precursor solution with seed crystals in a water bath and keep it at a constant temperature of 30°C. After the seed crystals undergo slight re-dissolution, they begin to grow. Observe the growth of the seed crystals.
[0063] When the size of the seed crystal does not change visible to the naked eye within S5.12h, a small hole with a diameter of 1 mm is punctured in the center of the sealing film with a needle. The solvent begins to evaporate, and the single crystal continues to grow. The growth of the single crystal is then observed.
[0064] When the size of the single crystal showed no visible change within 6.12 hours, the crystal was removed from the solution using clean stainless steel tweezers. After washing with isopropanol 3-5 times, the crystal was placed in a vacuum drying oven at 40°C for 4 hours, finally yielding (C) crystals with centimeter-sized crystals. 21 H 22 P)2Cu2I4 single crystal.
[0065] Figure 1 (C) prepared in Example 1 21 H 22 Crystal structure diagram of P)2Cu2I4 single crystal, [Cu2I4] 2- Inorganic clusters are large (C 21 H 22 P) + Separated by organic cations, they form a zero-dimensional structure, adjacent to [Cu₂I₄]. 2- The electron orbitals do not overlap, creating a strong quantum confinement effect.
[0066] Figure 2 Prepared for Example 1 (C) 21 H 22 A schematic diagram of the crystal growth process of P)2Cu2I4 single crystal. First, the first precursor solution rapidly evaporates to obtain several millimeter-sized single crystals (Ⅰ). Transparent seed crystals free of visible impurities and growth defects are selected and added to the second precursor solution (Ⅱ). After slight dissolution, the seed crystals continue to grow (Ⅲ). When the growth of the seed crystals is restricted, an opening is formed in the center of the sealing film, and the solvent begins to evaporate, inducing the single crystal to continue growing (Ⅳ). Finally, a crystal measuring 20×13×5mm is obtained.3 A transparent single crystal.
[0067] Figure 3 (a) is the (C) prepared in Example 1. 21 H 22 The simulated XRD patterns of single crystals, powders (the single crystals were ground into powders), and standard single crystal structures of the compound P)2Cu2I4 were highly consistent with the simulation results, indicating extremely high phase purity. The single crystals prepared in this invention belong to the same crystal phase as the standard phase, and the crystal symmetry is also completely consistent, so the crystal system (monoclinic) and space group (P21 / n) can be determined. The single crystals exhibited preferential growth of the (101) crystal plane. The unit cell parameters were: a=11.6046Å, b=12.3378Å, c=15.3372Å, α=90°, β=94.732°, γ=90°. (b) is the (C) prepared in Example 1. 21 H 22 The X-ray rocking curve of P)2Cu2I4 single crystal has a full width at half maximum (FWHM) of only 65.04″, indicating that the single crystal prepared by the crystal growth method in Example 1 has extremely high crystal quality.
[0068] Figure 4 (a) is the (C) prepared in Example 1. 21 H 22 The radioluminescence (RL) spectrum of a P)2Cu2I4 single crystal shows an emission peak at 443 nm, exhibiting the characteristics of (C)2Cu2I4 single crystal. 21 H 22 (a) P)2Cu2I4 single crystals emitted bright blue light under X-ray excitation at 50 kV and 80 μA; (b) The (C)2Cu2I4 single crystal prepared in Example 1 was evaluated. 21 H 22 (p) The light yield of the 2Cu2I4 single crystal is approximately 18184 ph / MeV; (c) indicates that the light yield of the 2Cu2I4 single crystal prepared in Example 1 is approximately 18184 ph / MeV; 21 H 22 The integrated RL intensity of P)2Cu2I4 single crystals showed a good linear correlation with the dose rate, and the calculated detection limit was 443.76 nGy / s; (d) is the (C) prepared in Example 1. 21 H 22 X-ray imaging of a P)2Cu2I4 single crystal key yields clear images and allows observation of the internal information of the imaged object, proving that (C) 21 H 22 P)2Cu2I4 single crystals have excellent X-ray imaging capabilities.
[0069] Example 2
[0070] A method for preparing a Cu(I)-based halide scintillation thin film for X-ray imaging includes the following steps:
[0071] S1. (C) 21 H 22 P)2Cu2I4 single crystal (0.7434 g), DMF (8.5 ml) and HCOOH (0.5 ml) were mixed in a 25 ml beaker, a magnetic stir bar was added, the beaker was sealed with a sealing film, and the beaker was placed on a magnetic stirrer and stirred at 600 r / min for 4 h in a water bath at 60 °C to dissolve the precursor solution.
[0072] S2. Add PMMA powder (2.5g) to the precursor solution obtained in S1, seal the end with a sealing film, place it on a magnetic stirrer, and stir at 600 r / min for 4 hours in a water bath at 60℃ to dissolve it, thus obtaining a latex suspension.
[0073] S3. Coat the latex-like suspension onto a quartz glass slide to form a film. After annealing at 80°C for 30 min, gently peel the film off the glass slide to obtain (C). 21 H 22 P)2Cu2I4@PMMA flexible scintillator film. Zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillator single crystals are uniformly distributed in a microcrystalline morphology within the PMMA matrix. During the annealing process, as the solvent evaporates, (C)2Cu2I4@PMMA flexible scintillator film... 21 H 22 P)2Cu2I4 recrystallizes in situ and precipitates. PMMA, as a long-chain polymer matrix, exhibits increased viscosity with solvent evaporation, which affects the precipitation of (C)2Cu2I4. 21 H 22 The P)2Cu2I4 microcrystals create a spatial confinement effect, uniformly encapsulating the microcrystals within the matrix and preventing further crystal growth and macroscopic aggregation, ultimately forming microcrystals uniformly dispersed in the PMMA matrix.
[0074] Figure 5 In Example 2 shown, (C) was prepared in situ using a blade coating method. 21 H 22 The P)2Cu2I4@PMMA flexible film exhibits high transmittance under ambient light and emits bright blue light when excited by X-rays.
[0075] Figure 6 (a) is the (C) prepared in Example 2. 21 H 22 (a) Imaging images of the P)2Cu2I4@PMMA flexible film against a standard line pair card (Type 39b) and intensity distribution curves at 8, 9, and 10 LP / mm, demonstrating a spatial resolution better than 10 LP / mm; (b) is the P)2Cu2I4@PMMA flexible film prepared in Example 2. 21 H 22The modulation transfer function (MTF) curves of P)2Cu2I4@PMMA flexible films obtained by the edge-cutting method show a spatial resolution of 10.7 LP / mm@MTF=0.2.
[0076] Figure 7 The (C) prepared in Example 2 is shown. 21 H 22 The P)2Cu2I4@PMMA flexible film can clearly distinguish the iron wires inside the capsule.
[0077] Figure 8 The (C) prepared in Example 2 is shown. 21 H 22 Underwater X-ray imaging of P)2Cu2I4@PMMA flexible thin film can clearly distinguish the internal structure of the chip, proving its ability to perform underwater X-ray imaging.
[0078] Comparative Example 1
[0079] The difference between Comparative Example 1 and Example 1 is that the traditional preparation process of Cu(I)-based halide scintillation single crystals only includes solvent evaporation growth and does not include the seed crystal-induced heat-holding growth stage. The specific preparation steps are as follows:
[0080] S1-S2 are exactly the same as steps S1-S2 in Example 1;
[0081] S3. Place C 21 H 22 PI powder (2 mmol, 0.8646 g), CuI powder (2 mmol, 0.3809 g), DMF (20.5 ml) and HCOOH (2 ml) were mixed in a 50 ml beaker, a magnetic stir bar was added, the beaker was sealed with a sealing film, and the beaker was placed on a magnetic stirrer and stirred at 600 r / min for 12 h in a water bath at 30 °C to dissolve the second precursor solution.
[0082] Using clean stainless steel tweezers, select transparent single crystals without visible impurities and growth defects from the millimeter-sized single crystals obtained in S2 as seed crystals. Place the seed crystals into the second precursor solution, seal the opening with a sealing film, and puncture the center of the sealing film to form an opening with a diameter of 1 mm.
[0083] S4. Place the precursor solution with seed crystals in a water bath and keep it at a constant temperature of 30°C until the solvent begins to evaporate. Observe the growth of seed crystals every 12 hours.
[0084] When no new crystal nuclei were observed to form within 5.12 hours and no visible growth of single crystals was observed, the crystals were removed from the solution using clean stainless steel tweezers. After washing with isopropanol 3-5 times, the crystals were placed in a vacuum drying oven at 40°C for 4 hours, finally yielding millimeter-sized (C) crystals. 21 H 22 P)2Cu2I4 single crystal.
[0085] Figure 9 The millimeter-sized (C) specimens prepared in Comparative Example 1 are shown. 21 H 22 In P)2Cu2I4 single crystal formation, severe secondary nucleation occurs in the solution, causing a large number of newly formed crystals to adhere to the seed crystal surface, hindering seed crystal growth. The resulting crystals are small in size, agglomerated, and contain numerous visible inclusion defects.
[0086] Comparative Example 2
[0087] The difference between Comparative Example 2 and Example 2 is that the traditional flexible scintillator film is usually prepared by directly grinding the light-emitting crystal into powder and then physically blending it with the polymer. The specific operation steps are as follows:
[0088] S1. (C) 21 H 22 A single crystal of P)2Cu2I4 (0.7434 g) was ground thoroughly in an agate mortar for 10 min to obtain (C)2Cu2I4 single crystal. 21 H 22 P)2Cu2I4 microcrystalline powder;
[0089] S2. (C) 21 H 22 P)2Cu2I4 microcrystalline powder (0.7434 g), PMMA powder (2.5 g), and p-xylene solution (5.5 ml) were mixed in a 25 ml beaker, a magnetic stir bar was added, the beaker was sealed with a sealing film, and the beaker was placed on a magnetic stirrer and stirred at 600 r / min at room temperature for 4 h to dissolve the mixture, resulting in a latex-like suspension.
[0090] S3. Coat the latex-like suspension onto a quartz glass slide to form a film. After annealing at 80°C for 30 min, gently peel the film off the glass slide to obtain (C). 21 H 22 P)2Cu2I4@PMMA flexible scintillator film.
[0091] Figure 10 The (C) prepared by physical blending in Comparative Example 2 shown below 21 H 22The P)2Cu2I4@PMMA flexible film exhibits significantly lower transmittance under ambient light compared to the in-situ composite film in Example 2. This is attributed to light scattering induced by internal aggregates of unevenly sized particles. Under X-ray excitation, the film displays a non-uniform radioluminescence intensity distribution. Figure 5 and Figure 10 The comparison reveals a significant difference in the uniformity of light emission between the two films, and uniform light emission is a prerequisite for achieving high-resolution X-ray imaging. In Comparative Example 2, the non-uniform particle agglomerates in the physically blended film induce severe light scattering, resulting in an uneven distribution of radiative emission intensity on the film surface. This easily causes uneven spots and artifacts in imaging. Since this optical scattering caused by internal particle agglomeration is a physical defect of the material itself and does not change with the external environment, the X-ray spatial resolution of the film prepared in Comparative Example 2 is inevitably much worse than that of Example 2, whether in an atmospheric environment or underwater.
[0092] In summary, this invention employs a gradient growth strategy combining seed crystal induction and solvent evaporation growth to successfully prepare (C) crystals with high crystal quality and centimeter-scale dimensions. 21 H 22 P)₂Cu₂I₄ scintillation single crystal was used, and its excellent X-ray imaging performance was confirmed. Furthermore, this invention also provides a (C)₂Cu₂I₄ scintillation single crystal that combines high transmittance with excellent water stability. 21 H 22 P)2Cu2I4@PMMA flexible composite film was successfully used to achieve high-resolution underwater X-ray imaging.
[0093] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the scope of the technology disclosed in the present invention, and such modifications or substitutions should all be covered within the scope of protection of the present invention.
Claims
1. A zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystal, characterized in that: Its chemical formula is (C 21 H 22 P)2Cu2I4, crystal system is monoclinic, space group is P21 / n; The scintillation single crystal is a bulk single crystal with a size on the order of centimeters, and has organic cations (C... 21 H 22 P) + isolation Zero-dimensional electronic structure formed by anion clusters.
2. The zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystal according to claim 1, characterized in that: The unit cell parameters of the scintillation single crystal are: a=11.6046Å, b=12.3378Å, c=15.3372Å, α=90°, β=94.732°, γ=90°; The half-width at half maximum (WHM) of the X-ray diffraction rocking curve of the (101) crystal plane of the scintillation single crystal is 65.04″.
3. The method for preparing zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystals according to claim 1, characterized in that, Includes the following steps: S1, Preparation of the first precursor solution C 21 H 22 PI and CuI are dissolved in a mixed solution of N,N-dimethylformamide and formic acid, sealed with a sealing film, and heated and stirred at 40-45℃ to obtain a nearly saturated first precursor solution. S2, Seed Crystal Acquisition The first precursor solution was filtered, sealed with a sealing membrane, and perforated on the sealing membrane. It was then volatilized at a constant temperature of 40-45℃ for 96-120 h to obtain single crystals of millimeter size. Single crystals were then selected from these to serve as seed crystals. S3, Micro-redissolution treatment The seed crystal is placed in a nearly saturated second precursor solution, sealed with a sealing film, and kept at a constant temperature of 30-35°C. After the seed crystal undergoes slight re-dissolution, it begins to grow. Among them, C 21 H 22 PI and CuI are dissolved in a mixed solution of N,N-dimethylformamide and formic acid, sealed with a sealing film, and heated and stirred at 30-35°C to obtain a second precursor solution. The second precursor solution has a concentration of C... 21 H 22 The molar concentration of PI in N,N-dimethylformamide is lower than that in the first precursor solution. 21 H 22 The molar concentration of PI in N,N-dimethylformamide; S4, Quasi-equilibrium growth After the seed crystal growth in S3 is restricted, a hole is made in the sealing film to allow the solvent to evaporate and single crystal growth to occur. After the single crystal growth is restricted, it is removed, washed, and vacuum dried to obtain centimeter-sized (C) crystals. 21 H 22 P)2Cu2I4 single crystal.
4. The method for preparing zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystals according to claim 3, characterized in that: In S1, C in the first precursor solution 21 H 22 The molar ratio of PI to CuI is 1:1; the volume ratio of N,N-dimethylformamide to formic acid is 9-18; C 21 H 22 The molar concentration of PI in DMF was 0.1-0.15 mol / L; the stirring method was magnetic stirring, the speed was set to 100-1000 r / min, the stirring time was 10-12 h, and water bath heating was used; In S2, the first precursor solution is filtered using an organic nylon-66 needle filter with a pore size of 0.22 μm; the size of the opening formed by the central puncture of the sealing membrane is 1-1.5 mm; it is volatilized at a constant temperature in a water bath; the seed crystal selection criteria are transparency and absence of visible impurities and growth defects; In S3, C in the second precursor solution 21 H 22 The molar ratio of PI to CuI is 1:1, the volume ratio of N,N-dimethylformamide to formic acid is 9-18, and C... 21 H 22 The molar concentration of PI in DMF is 0.05-0.1 mol / L; it is kept at a constant temperature in a water bath. In S4, the seed crystal growth restriction means that the seed crystal size does not change with the naked eye within 12 hours, and the size of the opening formed by the puncture in the center of the sealing film is 1-1.5 mm. The term "limited single crystal growth" refers to the absence of any visible change in single crystal size within 12 hours. The crystal is then removed from the solution, washed 3-5 times with isopropanol, and placed in a vacuum drying oven at 40-45°C for 4-6 hours.
5. A Cu(I)-based halide scintillation thin film, characterized in that: It is formed by dissolving the zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystal as described in claim 1 and then in situ combining it with a polymethyl methacrylate matrix.
6. The method for preparing the Cu(I)-based halide scintillation thin film according to claim 5, characterized in that, Includes the following steps: 1) Dissolve the Cu(I)-based halide scintillation single crystal of claim 1 in a mixed solution of N,N-dimethylformamide and formic acid, seal the solution with a sealing film, and heat and stir to obtain a precursor solution; 2) Add polymethyl methacrylate powder to the precursor solution, heat and stir to obtain a latex-like suspension; 3) The latex-like suspension is coated onto the substrate to form a film, which is then peeled off after annealing to obtain a Cu(I)-based halide scintillation film.
7. The method for preparing Cu(I)-based halide scintillation thin films according to claim 6, characterized in that: In step 1), the volume ratio of N,N-dimethylformamide to formic acid is 9-18, (C 21 H 22 The mass concentration of P)2Cu2I4 in N,N-dimethylformamide is 0.05-0.1 g / mL; the stirring method is magnetic stirring, the speed is set to 100-1000 r / min, the stirring time is 2-4 h, and the water bath heating is carried out at a temperature of 60-65℃. In step 2), polymethyl methacrylate powder and (C 21 H 22 The mass ratio of P)2Cu2I4 single crystals is 3-4. The stirring method is magnetic stirring, the speed is set to 100-1000 r / min, the stirring time is 2-4h, and water bath heating is used with a heating temperature of 60-65℃. In step 3), the annealing temperature is 75-80℃ and the annealing time is 20-30min.
8. The application of the zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystal as described in claim 1 in the fabrication of X-ray imaging devices.
9. The application of the Cu(I)-based halide scintillation thin film of claim 5 in X-ray imaging or the fabrication of X-ray imaging devices in air or underwater environments.
10. An X-ray imaging device, characterized in that: The detection material is the zero-dimensional organic-inorganic hybrid Cu(I)-based halide scintillation single crystal as described in claim 1 or the Cu(I)-based halide scintillation thin film as described in claim 5.